Bahasa Rupa Wimba dalam Komik “Flap Book” Anak-anak: Studi Analisis Isi - Ferry Darmawan (MediaTor (Jurnal Komunikasi), 2007)
Knowledge and technology development generate a modern means of mass media, such as photo, moving image, television. This development based on images, therefore, demanded the ability of image to tell stories of something. Around 80% of audiovisual information absorbs by human through visions. The fact was utilized to optimizing the process of children learning. Compared with writings, children learn better from pictures in order to grasp the meaning and concept. Wimba is a-picture-reading-methods for pre-school children. Flapbook is an example of book full of wimba discourse. Wimba itself was a term introduced for concrete images.